2021
DOI: 10.1098/rsos.201345
|View full text |Cite
|
Sign up to set email alerts
|

The everyday acoustic environment and its association with human heart rate: evidence from real-world data logging with hearing aids and wearables

Abstract: We investigate the short-term association between multidimensional acoustic characteristics of everyday ambient sound and continuous mean heart rate. We used in-market data from hearing aid users who logged ambient acoustics via smartphone-connected hearing aids and continuous mean heart rate in 5 min intervals from their own wearables. We find that acoustic characteristics explain approximately 4% of the fluctuation in mean heart rate throughout the day. Specifically, increases in ambient sound pressure inten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 59 publications
5
23
1
Order By: Relevance
“…In addition, for each log, the intrinsically accumulated hearing aid on-time (in seconds) since last clinical visit is stored. More details about the dataset can be found in Christensen et al ( 32 ). In all following analyses, only data logged between 6:00 and 00:00 are used.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, for each log, the intrinsically accumulated hearing aid on-time (in seconds) since last clinical visit is stored. More details about the dataset can be found in Christensen et al ( 32 ). In all following analyses, only data logged between 6:00 and 00:00 are used.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it has been used to establish evidence regarding daily hearing aid usage for public health decision-making ( 29 , 30 ), to augment EMA with hearing devices with acoustic information ( 21 , 25 ) and to support development of advanced hearing aid technology ( 31 – 34 ). Further, by combining remotely logged hearing aid data with that collected from fitness trackers it has been shown that heart rate is significantly and continuously moderated by dimensions of the ambient acoustic environment ( 32 ). Finally, remote data logging has also been introduced in a commercially available hearing aid for users to track their own hearing aid usage and sound exposure [HearingFitness™, ( 35 )].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, EMA data indicated that additional high-frequency gain resulted in real-world listening experiences that were judged as too loud, even for the pure speech soundscape. Thus, the data do not provide evidence for the hypothesized benefit in speech recognition from the availability of more high-frequency speech cues [9,43,45]. Instead, the results suggest that real-life experiences should be considered more closely when fitting high-frequency amplification in BCD users.…”
Section: Discussionmentioning
confidence: 92%
“…Many schools and universities are currently located in congested locations of cities, such as near marketplaces and restaurants, due to a lack of appropriate sites or the rapid growth of neighbouring viable school sites. Universities should ideally be in a calm setting since noise in the university environment affects activity within the university or school (Christensen, 2021). Therefore, the aim of this research is to assess noise pollution levels and their sources in some locations in the University of Zakho and their possible adverse effects on the populace in that selected region.…”
Section: -Introductionmentioning
confidence: 99%